RESERVOIR ROCKS IN IMPACT STRUCTURES: ELECTRICAL PARAMETERS - Vyzhva, S.; Mikhailov , V.; Onyshchuk, D.; Onyshchuk, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
There are 5 proven hydrocarbon sites associated with impact structures and 10 potential oil-and-gas bearing craters. The objective of the research is to estimate the petrophysical parameters of the reservoir rocks containing unconventional hydrocarbons – the prospective impact sites of the Ukrainian Shield. An account is given of the technique used and the results of petrophysical research on complex terrigenous reservoirs. A set of experimental laboratory studies included identifying the following: density of the studied rocks (dry and saturated with mineral oil), open porosity (by nitrogen and mineral oil saturation methods), residual water saturation factor (by centrifugation), permeability (method of stationary filtration of nitrogen), interval time and P-wave and S-wave velocities, resistivity and dielectric permittivity. Laboratory electrometric measurements of dry core samples were performed at a temperature of 20ºC using a laboratory electrometric set developed on the basis of a digital teraohmmeter SA 6547and RCL-meter MHC-1100 ensuring high-precision measurement of electrical resistance and capacity in the high frequency range using digital PC recording and special software. Laboratory electrometric measurements were performed on cylindrical rock samples (30 mm in diameter and 30 mm in height), these being a standard size and shape of the laboratory samples tested on the laboratory equipment for estimating the petrophysical parameters of rocks. The research results showed a correlation between the petrophysical parameters and rock capacity from the well intervals of impact structures having hydrocarbon prospects. The petrographic analysis of core samples showed that among the impact structures there dominate impactites, suevits, breccias and reworked gneisses. There have also been found inclusions of clay material, siderite, anthracolithization and pyritization. In addition, significant variations are observed in the resistivity values of the samples. Relative dielectric permittivity varies from 5.7 to 78.5. Low values of relative dielectric permittivity (40) maxima are found in breccias and gneisses from the Obolonska structure. We have shown the correlation dependences between the porosity factor, the residual water factor and the decimal logarithm of dielectric permittivity. This research was the first attempt to estimate the petroelectrical parameters and their correlation with the capacitive properties of rocks from the Ukrainian impact structures.
Keywords: impactites; suevits; reservoirs; porosity factor; permeability index; resistivity; dielectric permittivity